Room temperature polymerization of N-vinylcarbazole in tetrahydrofuran - Lyoo, WS; Kwak, JW; Noh, SK; Kim, DH; Lee, J; Kim, N; Park, KH; Lee, CJ (KOREAN FIBER SOCIETY, 2004)
N-Vinylcarbazole (VCZ) was solution-polymerized in tetrahydrofuran (THF) at 25, 35, and 45 degreesC using a room temperature initiator, 2,2'-azobis(2,4-dimethylvaleronitrile) (ADMVN); the effects of amount of solvent, polymerization temperature, and initiator concentration were investigated. On the whole, the experimental results corresponded to predicted ones. Room polymerization temperature using ADMVN proved to be successful in obtaining poly(N-vinylcarbazole) (PVCZ) of high molecular weight with small temperature rise during polymerization, nevertheless of free radical polymerization by azoinitiator. The polymerization rate of VCZ in THF was proportional to the 0.47 power of ADMVN concentration. The molecular weight was higher and the molecular weight distribution was narrower with PVCZ polymerized at lower temperatures. For PVCZ prepared in THF at 25 degreesC using ADMVN concentration of 0.00005 mol/mol of VCZ. weight-average molecular weight of 221,000 was obtained, with polydispersity index of 2.05, and degree of lightness converged to about 99%.
Keywords: CATIONIC POLYMERIZATION; PHOTOCATIONIC POLYMERIZATION; ELECTROLUMINESCENT DEVICES; PHOTOREFRACTIVE POLYMER; PHASE-STABILITY; TRITYL SALTS; POLY(N-VINYLCARBAZOLE); FILMS; AZOBISISOBUTYRONITRILE; DEPENDENCE